2009
DOI: 10.1103/physrevlett.102.125503
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Phonon-Surface Roughness Scattering on Thermal Conductivity of Thin Si Nanowires

Abstract: We present a novel approach for computing the surface roughness-limited thermal conductivity of silicon nanowires with diameter D<100 nm. A frequency-dependent phonon scattering rate is computed from perturbation theory and related to a description of the surface through the root-mean-square roughness height Delta and autocovariance length L. Using a full phonon dispersion relation, we find a quadratic dependence of thermal conductivity on diameter and roughness as (D/Delta)(2). Computed results show excellent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
310
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(326 citation statements)
references
References 24 publications
15
310
1
Order By: Relevance
“…24,25,26,27,28 The thermoelectric phenomenon can be utilized to harvest otherwise wasted thermal energy directly into electric power. To increase the thermoelectric efficiency, the thermal conductivity in NWs should be reduced, which can be realized through phonon confinement effects, 29,30,31,32 isotope doping, 33 surface roughness, 34,35,36 or non-planar (kinked) structures. 37 Shi et al suggested enhancing the thermoelectric efficiency through gallium doping, and the thermoelectric figure of merit was found to be increased by a factor of 2.5 at 4% gallium doping.…”
Section: Introductionmentioning
confidence: 99%
“…24,25,26,27,28 The thermoelectric phenomenon can be utilized to harvest otherwise wasted thermal energy directly into electric power. To increase the thermoelectric efficiency, the thermal conductivity in NWs should be reduced, which can be realized through phonon confinement effects, 29,30,31,32 isotope doping, 33 surface roughness, 34,35,36 or non-planar (kinked) structures. 37 Shi et al suggested enhancing the thermoelectric efficiency through gallium doping, and the thermoelectric figure of merit was found to be increased by a factor of 2.5 at 4% gallium doping.…”
Section: Introductionmentioning
confidence: 99%
“…They have also attracted wide attention in thermoelectric applications because of their remarkable improved thermoelectric figure of merit, which is mainly caused by the significant reduction of thermal conductivity in SiNWs [4,5]. Many approaches have been proposed to further reduce thermal conductivity of SiNWs, such as introduction of impurity scattering [6,7], holey structure [8][9][10], and surface roughness [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…12 As a nanostructure gets smaller, its thermal conductivity is reduced due to more frequent scattering between phonons and the system boundaries. [1][2][3][4][5][6][7][8][9][10][11] For very small systems (e.g., silicon films thinner than 20 nm), changes in the phonon density of states also affect thermal transport. 2,6,8 Our interest here is nanostructures large enough that the phonon density of states is bulk-like.…”
mentioning
confidence: 99%
“…As the dimensions of electronic, optoelectronic, and energy conversion devices are reduced, the thermal conductivities of the device components (e.g., thin films and nanowires) are also reduced. [1][2][3][4][5][6][7][8][9][10][11] The large electrical power densities in such devices cause Joule heating and the reduced thermal conductivities can lead to high operating temperatures, sub-optimal performance, and poor reliability. Predicting the thermal conductivity reduction in nanostructures is thus a critical part of developing next-generation thermal management strategies.…”
mentioning
confidence: 99%